Health Indicator System - Mat Nanyan, Najmuddin Salmi (Universiti Sains Malaysia, 2006)
The desire for comfort, efficient service, reliable system and precise information are among the characteristics of human needs today. Fortunately these needs can be fulfilled by using technology. This shows that technology plays a vital role in human life. Medical field is also influenced by technology. Health consciousness is becoming one of the major issue in our life today as well as other needs. There is no argument that whenever we develop our country physically, the rate of disease increases equally. Both parties standing at parity. So the health conscious attitude must be in our people mind. The simplest step that can be taken to avoid disease is by monitoring the human health parameters, for instance pulse rate, body temperature and blood pressure. The parameters may indicate our health level. In a simple word, this system developed in aiming to build a system that can collect health parameters and display it at the user interface software. This system consists of the combination of hardware and software. Hardware are the circuits that process the analog signal and software is the medium that display the result and provide a path for interaction between user and system. The software was developed using Visual Basic 6.0.